Psychological research on human intelligence: 20th century revisited at the dawn of the Third Millennium - Miranda, Maria José (2000)
Human intelligence is a recurrent issue along the centuries in western culture. Also, it is a recurrent issue in the history of psychology. Conceptual descriptions along the 20th century are analysed, and main paradigms (biological, differential, genetic, computational) examined. Research on human intelligence in the third millennium will focus upon paths definitely open in the 90s, such as an interdisciplinary approach and emotional and functional aspects of intelligent behavior. The general framework will be, however, new: the globalization, its challenges and risks.